Synthesis, Characterization and Bioactivity Evaluation for Some Metal Ions Complexes with New Ligand Derived from 2-hydroxy-1- napthaldehyed (Baghdad Science Journal, 2024)
The newly synthesized Schiff base ligand (E)-2-((2-phenylhydrazono)methyl)naphthalen-1-ol (phenyl hydrazine derivative), is allowed to react with each of the next mineral ion: Ni2+, Cu2+, Zn2+andCd2+successfully resulting to obtain new metal complexes with different geometric shape. The formation of Schiff base complexes and also the origin Schiff base is indicated using LC-Mass that manifest the obtained molar mass, FT-IR proved the occurrence of coordination through N of azobenzene and O of OH by observing the shifting in azomethines band and appearing of M-N and N-O bands. Moreover, we can also detect by such apparatus, the presence of aquatic water molecule inside the coordination sphere. UV-Vis spectra of all resultants revealed the creation of coordination by noticing the shifting in electronic transitions that happened in ligand at ultra violet region. TGA and DSC measurements for ligand and Ni-complex also prove the complexation and presence of coordinated water molecule inside the coordination sphere. In addition, molar accessibility and FAA results were closer to the counting results. The diagnoses return gave mononuclear complexes, bidentate dental behavior and tetrahedral geometry for all complexes. Depending on the antibiotic property of Schiff base and its complexes, we have tested such property on various types of microorganisms as detailed in the paper.